Evaluating different methods for elevation calibration of MAX-DOAS (Multi AXis Differential Optical Absorption Spectroscopy) instruments during the CINDI-2 campaign - Donner, Sebastian; Kuhn, Jonas; Roozendael, Michel Van; Bais, Alkiviadis; Beirle, Steffen; Bösch, Tim; Bognar, Kristof; Bruchkouski, Ilya; Chan, Ka Lok; Dörner, Steffen; Drosoglou, Theano; Fayt, Caroline; et al. (Atmospheric measurement techniques, 2020)
Abstract. We present different methods for in-field elevation calibration of MAX-DOAS (Multi AXis Differential Optical Absorption Spectroscopy) instruments that were applied and inter-compared during the second Cabauw Intercomparison campaign for Nitrogen Dioxide measuring Instruments (CINDI-2). One necessary prerequisite of consistent MAX-DOAS retrievals is a precise and accurate calibration of the elevation angles of the different measuring systems. Therefore, different methods for this calibration were applied to several instruments during the campaign, and the results were inter-compared. This work first introduces and explains the different methods, namely far- and near-lamp measurements, white-stripe scans, horizon scans and sun scans, using data and results for only one (mainly the Max Planck Institute for Chemistry) instrument. In the second part, the far-lamp measurements and the horizon scans are examined for all participating groups. Here, the results for both methods are first inter-compared for the different instruments; secondly, the two methods are compared amongst each other. All methods turned out to be well-suited for the calibration of the elevation angles of MAX-DOAS systems, with each of them having individual advantages and drawbacks. Considering the results of this study, the systematic uncertainties of the methods can be estimated as ±0.05∘<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="35pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="0529566949cecaef9f603bb0b469e49e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-13-685-2020-ie00001.svg" width="35pt" height="11pt" src="amt-13-685-2020-ie00001.png"/></svg:svg> for the far-lamp measurements and the sun scans, ±0.25∘<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="35pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="1f32e1dc5553e330024d85314b228ea2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-13-685-2020-ie00002.svg" width="35pt" height="11pt" src="amt-13-685-2020-ie00002.png"/></svg:svg> for the horizon scans, and around ±0.1∘<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="989f69b6e9ff3ac9d4c1f98eb43ca5b4"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-13-685-2020-ie00003.svg" width="29pt" height="11pt" src="amt-13-685-2020-ie00003.png"/></svg:svg> for the white-stripe and near-lamp measurements. When comparing the results of far-lamp and horizon-scan measurements, a spread of around 0.9∘ in the elevation calibrations is found between the participating instruments for both methods. This spread is of the order of a typical field of view (FOV) of a MAX-DOAS instrument and therefore affecting the retrieval results. Further, consistent (wavelength dependent) offsets of 0.32∘ and 0.40∘ between far-lamp measurements and horizon scans are found, which can be explained by the fact that, despite the flat topography around the measurement site, obstacles such as trees might mark the visible horizon during daytime. The observed wavelength dependence can be explained by surface albedo effects. Lastly, the results are discussed and recommendations for future campaigns are given.